2017
DOI: 10.1371/journal.pone.0178553
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of a new formulation of micronized and ultramicronized N-palmitoylethanolamine in a tibia fracture mouse model of complex regional pain syndrome

Abstract: Complex regional pain syndrome type 1 (CRPS-I) is a disabling and frequently chronic condition. It involves the extremities and is a frequent consequence of distal tibia and radius fractures. The inflamed appearance of the affected CRPS-I limb suggests that local production of inflammatory mediators may be implicated in the ensuing etiology. A rodent tibia fracture model, characterized by inflammation, chronic unilateral hindlimb warmth, edema, protein extravasation, allodynia and hyperalgesia resembles the cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 41 publications
1
28
0
Order By: Relevance
“…PEA has no unfavorable effects at pharmacological doses [97]. In addition, several experimental works showed the beneficial effects of new PEA formulations (micronized or ultramicronized) in carrageenan-induced inflammation [98] on cognitive decline associated to neuropathic pain [99] in an Alzheimer disease model [100], tibia fracture mouse model [101], and diabetic neuropathy [102]. Recent observational clinical studies reported the beneficial use of ultramicronized PEA as an add-on therapy in patients suffering from low back pain [103] as well as in patients suffering from fibromyalgia syndrome (FMS) [104].…”
Section: New Therapeutic Strategiesmentioning
confidence: 99%
“…PEA has no unfavorable effects at pharmacological doses [97]. In addition, several experimental works showed the beneficial effects of new PEA formulations (micronized or ultramicronized) in carrageenan-induced inflammation [98] on cognitive decline associated to neuropathic pain [99] in an Alzheimer disease model [100], tibia fracture mouse model [101], and diabetic neuropathy [102]. Recent observational clinical studies reported the beneficial use of ultramicronized PEA as an add-on therapy in patients suffering from low back pain [103] as well as in patients suffering from fibromyalgia syndrome (FMS) [104].…”
Section: New Therapeutic Strategiesmentioning
confidence: 99%
“…Normalize the functional post-inflammatory accelerated intestinal transit [192] Colitis Mice Improve symptoms of colitis [191] Dermatitis Dogs Reduce pruritus and skin lesions [194] Contrast-agent-induced nephropathy Rats Prevent nephropathy in and alteration of biochemical parameters [195] Idiopathic pulmonary fibrosis Mice Reduces lung inflammation [196] Tibia fracture model Mice Decrease mast cell density, nerve growth factor, matrix metalloproteinase 9, and cytokines expression [197] Alzheimer's disease Mice Normalize astrocytic function, rebalance glutamatergic transmission, and restrain neuroinflammation [198] Joint pain Rats Reduce igeminal nerve sensitization [199] In neurological diseases, increases in PEA levels were observed in the patients liquor with schizophrenia, chronic migraine, and multiple sclerosis [200][201][202]. In multiple sclerosis, the levels of PEA also increased in plasma [203].…”
Section: Pea: Role In Pathological and Physiological Conditionsmentioning
confidence: 99%
“…In the same conditions, therapy with PEA-m allows for a considerable reduction of the use of nonsteroidal anti-inflammatory drugs NSAIDs, suggesting the possibility of simultaneous use in order to reduce the use of NSAIDs, which if taken for long periods, can induce significant side effects [210]. The results obtained in patients with low back pain have also been confirmed on a large number of patients with different chronic pain pathological conditions, such as radiculopathy, osteoarthritis, joint pain, tibia fracture, spinal surgical failure, post herpetic neuropathy, diabetic neuropathy, and oncological pain [197,199,209,212,213] (Table 3). Peripheral diabetic neuropathy Reduce pain symptoms characteristic of diabetic neuropathy [213] Carpal tunnel syndrome Improve sleep quality, confirming a correlation between sleep disorders and pain intensity [208] Moreover, Evangelista et al reported that in patients affected by carpal tunnel syndrome, the oral administration of ultramicronized PEA improved sleep quality, verifying a correlation between sleep disorders and pain intensity [208].…”
Section: Pea: Ultramicronization Processmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors would like to correct the following mistakes which were inadvertently included in the publication [ 1 ].…”
mentioning
confidence: 99%